2018
DOI: 10.1007/s11524-017-0225-3
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Non-injection Drug Use Associated with Injection Cessation among Street-Involved Youth in Vancouver, Canada

Abstract: Although abstinence from drug use is often a key goal of youth substance use treatment, transitioning to less harmful routes and types of drug use is desirable from both a clinical and public health perspective. Despite this, little is known about the trajectories of youth who inject drugs including changes in patterns of non-injection drug use. The At-Risk Youth Study (ARYS) is a longitudinal cohort of street-involved youth who use drugs in Vancouver, Canada. We used linear growth curve modeling to compare ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…One recent study among the same cohort of youth found that cessation of some forms of high intensity drug use (e.g. injection drug use) may occur while youth continue to use other, less harmful, forms of drugs such as cannabis . This suggests that non‐abstinence models may be suitable for some, and indeed many countries have accepted managed use as a treatment outcome goal in certain cases .…”
Section: Discussionmentioning
confidence: 99%
“…One recent study among the same cohort of youth found that cessation of some forms of high intensity drug use (e.g. injection drug use) may occur while youth continue to use other, less harmful, forms of drugs such as cannabis . This suggests that non‐abstinence models may be suitable for some, and indeed many countries have accepted managed use as a treatment outcome goal in certain cases .…”
Section: Discussionmentioning
confidence: 99%
“…Further research is needed to understand how the use of cannabis among youth experiencing street entrenchment might be protective in our and other similar settings in the context of the current crisis. At minimum, we must acknowledge cannabis use as an emic harm reduction and treatment strategy that is commonly employed among some highly vulnerable youth to facilitate periods of transition away from what are perceived as more dangerous forms and modes of drug use, resulting in significant-albeit usually intermittent-reductions in risk and harm from both an emic and public health perspective [36,54].…”
Section: Plos Onementioning
confidence: 99%
“…This phenomenon has been observed in several contexts. For example, in Canada, one study found that 63% of people who were actively injecting drugs reported the concurrent smoking of crack cocaine [ 7 ]. In Australia, a similar phenomenon has been seen with the co‐occurrence of smoking and injecting methamphetamine amongst people entering treatment for methamphetamine use [ 8 ], amongst community samples of people who inject methamphetamine [ 9 ] and people who inject drugs more broadly [ 10 ].…”
Section: Introductionmentioning
confidence: 99%